Distribution of Cambrian Source Rock Controlled by the Inherited Paleotopography on the Precambrian Basement in the Tarim Basin, NW China - Yuan, Haowei; Chen, Shuping; Dai, Kun; Guo, Xiaochen; Kong, Linghua; Feng, Nana; Zhao, Huaibo; Yang, Weili (Frontiers in Earth Science, 2022)
The Cambrian source rock is a key indicator that will guide future hydrocarbon explorations in ultra-deep strata. Despite its importance, the characteristics of paleotopography on the Precambrian basement and the distribution of source rocks above it remain unclear. The seismic and borehole data, isopach data, and the unconformity analysis are used to study the relations of the Cambrian source rock distribution to the paleotopography. The consistency of the strata thickness distribution maps of the Nanhua–Cambrian sequences show that the extensive thermal subsidence lasted the whole Sinian period, and makes the paleotopography of the Precambrian basement inherited from the landform after the Nanhua continental rifting. A major transgression caused by rapid subsidence of the Tarim Basin took place during the Cambrian. Shales were deposited offshore along the slopes of a paleo-uplift on the inherited paleotopography and formed the onlap in seismic profiles. The onlap on the inherited paleotopography reflects the distribution range of Yuertusi source rocks in the Cambrian.